Impact of Gender and Mother Tongue on the Uses of Articles - Kiruthikadevi, K. (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
The Indian English language teaching emphasizes the written rather spoken form. The present study, titled ‘Impact of Gender and Mother Tongue on the Uses of Articles,’ illustrates this. We investigated the perception of students in and around the Coimbatore district, who are post-graduate students of M.A English Literature from government-aided and private colleges. By using a researcher-constructed questionnaire, the ability of the sample to identify, produce and omit articles in selected forty contexts was analyzed. The results were analyzed through t tests, One – Way ANOVA, Correlation tests and Association tests. Results: Mother Tongue plays an important role in recognizing and producing the uses of the articles selected for this investigation. Gender has a major effect on the ability of women to recognize and develop the uses of the articles. From the result of this study, it proves the correlation between the understanding of usages and uses of the rules of grammar in the application.